Security Technology - Zaru, Adil Jamil (International Journal of Computer Sciences and Engineering, 2025)
All input is evil until proven otherwise!‖”so security technology come into play.With the rapid growth of interest in the Internet, network security has become a major concern to companies throughout the world. The fact that the information and tools needed to penetrate the security of corporate networks are widely available has increased that concern. Because of this increased focus on network security, network administrators often spend more effort protecting their networks than on actual network setup and administration. Tools that probe for system vulnerabilities, such as the Security Administrator Tool for Analyzing Networks (SATAN), and some of the newly available scanning and intrusion detection packages and appliances, assist in these efforts, but these tools only point out areas of weakness and may not provide a means to protect networks from all possible attacks. Thus, as a network administrator, you must constantly try to keep abreast of the large number of security issues confronting you in today's world. This paper describes many of the security issues that arise when connecting a private network. Understand the types of attacks that may be used by hackers to undermine network security. For decades, technology has transformed almost every aspect of business, from the shop floor to the shop door. While technology was a fundamental enabler, it was often driven from an operational or cost advantage and seen as separate from business itself. The new reality is that technology doesn’t support the business—technology powers the business. IT risks are now business risks and IT opportunities are now business opportunities.